2017
DOI: 10.1053/j.ajkd.2016.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Three Versus 4 Daily Exchanges and Residual Kidney Function Decline in Incident CAPD Patients: A Randomized Controlled Trial

Abstract: In this small trial, CAPD regimens with 3 and 4 exchanges had similar effects on residual GFR, urine volume, and time to anuria. Incremental peritoneal dialysis starts appear safe when patients are monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 41 publications
2
58
0
Order By: Relevance
“…Published studies of incremental dialysis have suggested a positive impact on patient quality of life due to lesser burden of dialysis procedures, enabling a more gradual, palatable immersion to dialysis initiation (27,28). They have also demonstrated reduced peritonitis rates attributed to decreased manual connections and an extended peritoneal "dry period," lower systemic and peritoneal glucose exposure (improved preservation of peritoneal membrane function and fewer metabolic alterations), and better preservation of RKF (22,27,29,30). These benefits have the potential of not only improving uptake of PD (27), but also enhancing both technique and patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies of incremental dialysis have suggested a positive impact on patient quality of life due to lesser burden of dialysis procedures, enabling a more gradual, palatable immersion to dialysis initiation (27,28). They have also demonstrated reduced peritonitis rates attributed to decreased manual connections and an extended peritoneal "dry period," lower systemic and peritoneal glucose exposure (improved preservation of peritoneal membrane function and fewer metabolic alterations), and better preservation of RKF (22,27,29,30). These benefits have the potential of not only improving uptake of PD (27), but also enhancing both technique and patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Accessing the peritoneum fewer times per day decreases the opportunity for the entry of infectious organisms and reduces the risk of peritonitis. A randomized, controlled trial of 139 patients followed over 2 years demonstrated that three-exchanges per day PD (incremental PD) was associated with a longer peritonitis-free survival compared with fourexchanges per day PD ("full-dose" PD) (5). Although this was a secondary outcome of the trial, the potential for prolonging peritonitis-free survival warrants further consideration.…”
Section: Incremental Peritoneal Dialysis To Optimize Advancing Americmentioning
confidence: 99%
“…Over the course of the last decade, more clinical experience on PD has been shared ( Figure 1a), including patient education, center management practices, and clinical strategies (such as 3 vs 4 exchanges, the "satellite PD center" model, etc.) aimed at improving clinical outcomes (16,(25)(26)(27)(28)(29)(30)(31)(32). It is worth noting that clinical outcomes from some PD centers are comparable with or even superior to their Western counterparts (15,16,18,19,22).…”
Section: Growth Of Chinese Pd Research Internationally and Locallymentioning
confidence: 99%